Defining and identifying critical elements of, and lessons learned from addressing, 'operational readiness' for public health emergency events, including COVID-19: a scoping review protocol. Issue 9 (19th September 2022) - English, Rene; Yauka Nyasulu, Juliet Charity; Berner, Karina; Geduld, Heike; McCaul, Michael; Joseph, Conran; Pappin, Michele; Gobat, Nina; Boulanger, Linda Lucy; Louw, Quinette
Abstract : Introduction: Much is known around public health preparedness and response phases. However, between the two phases is operational readiness that comprises the immediate actions needed to respond to a developing risk or hazard. Currently, emergency readiness is embedded in multiple frameworks and policy documents related to the health emergency cycle. However, knowledge about operational readiness' critical readiness components and actions required by countries to respond to public health eminent threat is not well known. Therefore, we aim to define and identify the critical elements of 'operational readiness' for public health emergencies, including COVID-19, and identify lessons learnt from addressing it, to inform the WHO Operational Readiness Framework. Methods and analysis: This is a scoping review following the Joanna Briggs Institute guidance. Reporting will be according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist. MEDLINE, Embase and Web of Science databases and grey literature will be searched and exported into an online systematic review software (eg, Rayyan in this case) for review. The review team, which apart from scoping review methodological experts include content experts in health systems and public health and emergency medicine, prepared an a priori study protocol in consultation with WHO representatives. ATLAS.ti V.9 will be used to conduct thematic data analysis as well as store, organise and retrieve data. Data analysis and presentation will be carried out by five reviewers. Ethics and dissemination: This review will reveal new insights, knowledge and lessons learnt that will translate into an operational framework for readiness actions. In consultation with WHO, findings will be disseminated as appropriate (eg, through professional bodies, conferences and research papers). No ethics approvals are required as no humans will be involved in data collection. Protocol registration: This rapid scoping review has been registered on Open Science Framework (doi:10.17605/OSF.IO/6SYAH).